Analisis Hasil Ujian Nasional Sekolah Menengah Kejuruan di Kota Makassar Menggunakan Linear Mixed Model Regression - Setiawan, Iman; Pannu, Abdullah (Department of Mathematics, Universitas Negeri Gorontalo, 2024)
Graduates of Vocational High Schools (SMK) in South Sulawesi Province, especially Makassar City, have a higher Open Unemployment Rate (TPT) than other levels of education. In fact, during the 2016-2020 period, various education management policies such as the revitalization of SMKs, the arrangement of study groups and the accreditation of SMK Education Units were held to encourage increased competence of graduates and the quality of SMK Education. The purpose of this study is to see how the pattern of National Examination (UN) results for SMKs in Makassar City in 2018-2020 and whether there are differences in the pattern of UN results for SMK accreditation. Because the analysis was carried out in multi years, the analysis was carried out using the Linear Mixed Model (LMM). Modeling is carried out in stages using 4 model schemes. This research shows that there has been a decrease in the SMK National Exam results in Makassar City in 2018-2020. In 2018, 2019 and 2020 each has an average of 52.26, 50.33 and 46.50. When viewed based on SMK accreditation, it can be seen that the decline in SMK National Examination results only occurs in SMKs that are not accredited A. This shows that policies related to increasing the competence of graduates and the quality of SMK education, especially in Makassar City, have no impact or even cannot be implemented properly for SMKs with accreditation other than A.